Financing the Missing Middle: A Systematic Review of Constraints and Solutions for SMES in Tanzania’s Blue Economy - Issa G Ahmed; Mbara Cham; Bakari K. Faki; Mohamed Abasi Hamad (Journal of Maritime Policy Science, 2026)
The strategic development of the Blue Economy (BE) is central to Tanzania’s national and regional aspirations for inclusive growth and poverty reduction, with small and medium-sized enterprises (SMEs) constituting its operational backbone. However, the transformative potential of BE sectors fisheries, aquaculture, coastal tourism, and maritime services is critically constrained by a persistent financing gap. This systematic review synthesizes current evidence to diagnose the binding financial constraints faced by BE-SMEs in Tanzania and to evaluate viable pathways for intervention. Employing a structured methodology, the review critically analyzes peer-reviewed literature, policy documents, and institutional reports from 2006 to 2025. The synthesis identifies a consistent quartet of barriers: stringent collateral requirements underpinned by information asymmetry, elevated lender risk perceptions due to sectoral volatility and climate exposure, pervasive deficiencies in SME financial records and business planning, and cumbersome loan application procedures. Concurrently, the analysis surfaces converging opportunity domains, including the adaptation of group-based and credit-guarantee mechanisms, the deployment of digital and alternative data for risk assessment, and the design of financial products tailored to seasonal cash flows. The review concludes that bridging the finance chasm requires a systemic shift towards blended financial instruments, policy-driven credit infrastructure improvements, and lender innovations in underwriting technology. By aligning financial systems with the distinct realities of BE-SMEs, Tanzania can unlock sustainable, equitable growth within its ocean-based economy.